OPTN/SRTR 2020 Annual Data Report: Liver. (10th March 2022) - Kwong, A. J.; Ebel, N. H.; Kim, W. R.; Lake, J. R.; Smith, J. M.; Schladt, D. P.; Skeans, M. A.; Foutz, J.; Gauntt, K.; Cafarella, M.; Snyder, J. J.; Israni, A. K.; et al.
Abstract: This year was marked by the COVID‐19 pandemic, which altered transplant program activity and affected waitlist and transplant outcomes. Still, 8906 liver transplants were performed, an all‐time high, across 142 centers in the United States, and pretransplant as well as graft and patient survival metrics, continued to improve. Living donation activity decreased after several years of growth. As of June 30, 2020, 98989 liver transplant recipients were alive with a functioning graft, and in the context of increasing liver transplant volume, the size of both the adult and pediatric liver transplant waitlists have decreased. On February 4, 2020, shortly before the pandemic began, a new liver distribution policy based on acuity circles was implemented, replacing donor service area‐ and region‐based boundaries. A policy change to direct pediatric livers to pediatric recipients led to an increase in deceased donor transplant rates and a decrease in pretransplant mortality rate among children, although the absolute number of pediatric transplants did not increase in 2020. Among adults, alcohol‐associated liver disease became the predominant indication for liver transplant in 2020. After implementation of the National Liver Review Board and lower waitlist priority for most exception cases in 2019, fewer liver transplants were being performed via exception points, and the transplant rate between those with and without hepatocellular carcinoma has equalized. Women continue to experience higher pretransplant mortality and lower rates of liver transplant than men.